A Framework for Implementing National Respiratory Guidelines in Wales - RHYS JEFFERIES (2023)
Introduction: Implementation outcomes are necessary to experience clinical impact of interventions in the real world. Clear synergy exists between evidence-based clinical recommendations in clinical guidelines and the evidence-based process of implementing them, however less than a quarter of clinical guidelines are implemented using a framework. Methods: Critical review and analysis of the published literature provided the basis for developing framework constructs to facilitate the process of implementing national clinical guidelines in Wales. This is an observational assessment using mixed methods to assess the acceptability and adoption of novel national clinical guidelines in Wales. The framework is adapted in preparation for formal validation. Results: A conceptual framework for implementing clinical guidelines at scale was developed from the literature and findings from thematic analysis of potential guideline adopters in Wales. This was deemed relevant to wider strategies and was therefore applied to the implementation of novel asthma/COPD and COVID-19 guidelines. Applying the framework demonstrated widespread acceptance and adoption of the guidelines across all Health Boards in NHS Wales, however evidence of widespread adherence of the guidelines with fidelity remains unproven as this requires longitudinal observation of process and clinical outcome benefits relating to each guideline recommendations. Conclusions: The differentiation of contexts between the two case studies presented here highlights the difference in pace and urgency of implementation to optimise penetration of a guideline 23 implementation strategy across a target population in Wales. It addresses much of the ambiguity of definitions and joins common principles to create a framework that can be recommended for further testing with other clinical specialities and contexts outside of Wales. Whilst the COVID-19 pandemic introduced a major barrier to guideline adoption for asthma and COPD, it also presented a unique scenario that stimulated large-scale use of a novel COVID guideline. Whilst it was too soon to explore the correlation between implementation strategies, guideline adherence, and clinical outcomes – achieving acceptance and adoption of the guidelines lays the foundations for further exploration of social benefits on a national scale.